Blending creativity and connectivity: A Treffinger-based cooperative learning model using Facebook - Indrawati, Ena Suma; Festiyed, Festiyed; Ratnawulan, Ratnawulan (International Journal of Innovative Research and Scientific Studies, 2025)
This study develops and evaluates a cooperative learning model based on Treffinger’s framework, integrated with blended learning and Facebook, to enhance the creative thinking of university students. Addressing challenges in traditional instruction—limited flexibility, low interactivity, and minimal support for creativity- the model follows a structured educational design research approach, including validation, prototyping, and field testing phases. Conducted within a physics education course at Universitas Adzkia, the study involved 72 undergraduate students and five expert validators. The model combines face-to-face and online components, utilizing Facebook as a platform for accessible interaction, collaboration, and reflection. Findings indicate high content validity (Cronbach’s α = 0.894), strong practicality ratings, and significant improvement in creative thinking skills fluency, flexibility, originality, and elaboration based on pre- and post-test comparisons (p < 0.001). Qualitative insights further reveal enhanced student engagement, confidence, and collaborative behavior, with Facebook’s asynchronous discussion features fostering a more inclusive and student-centered learning experience. The study concludes that integrating the Treffinger model within a Facebook-based blended framework presents an effective, scalable, and cost-efficient approach to fostering creativity in higher education, with broad applicability across disciplines. This research contributes to digital pedagogy, instructional innovation, and 21st-century skills development in teacher education.